Personnel and Industrial Relations : A Managerial Approach - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Personnel and Industrial Relations : A Managerial Approach" by John B. Miner.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z